Design and Implementation of Solar Charge Controller with P&O MPPT for Light-Fishing in Ujung Pangkah, Gresik - Wahyu Ardi Santosa; Sjamsjul Anam; Feby Agung Pamuji (JAREE (Journal on Advanced Research in Electrical Engineering), 2020)
Bagan tancap is a conventional fishing using diesel as its main source. This conventional method needs to be replaced with an eco-friendly and easy to use system, namely solar panels. The solar panels power is just limited by time so the stability of the system is poorly maintained that needs to be a battery as a storage of energy to improve system stability. However, the power that is not optimal causes the charging battery to take longer and not be constant with periods of weather and irradiation coditions. The charging battery without MPPT it tends not to be optimal because the solar panel does not operate at its maximum value. MPPT with perturb and observe algorithms can maximize power on solar cells with tracking speeds that depend on the response speed of the converter. While boost coverter has the ability to maintain potential differences that are tailored to the battery specifications and keep the current and voltage ripple values relatively small. For this reason, this final project will design and implement solar charge controller equipped with MPPT P & O (Perturb and Observe) and boost converter, this method can maximize the power of the solar panel by 97.84% with a faster charging time for 27 minutes.Keywords: light fishing, MPPT, perturb and observe, solar charge controller.